2016
DOI: 10.1055/s-0036-1582233
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Facial Lipofilling on Patient-Perceived Improvement in Facial Appearance and Quality of Life

Abstract: An investigation of the effect of facial lipofilling on patient's satisfaction is a challenging and ongoing research area. Therefore, the aim of this study was to investigate the impact of aesthetic intervention on self-perceived improvement in facial appearance and quality of life (QoL) after 1- and 6-month follow-ups. In the period from October 1, 2014, to March 1, 2015, a total of 63 consecutive subjects who underwent a facial lipofilling were included in the study. The satisfaction with facial appearance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…All articles described, to some extent, the methods of preparing and grafting the adipose tissue (Table 2 ). 9 , 35 , 36 , 38 52 Eleven out of 14 studies used a local form of anesthesia, 9 , 36 , 38 42 , 44 46 , 48 , 49 , 51 , 52 and 3 authors preferred general anesthesia. 35 , 47 , 50 The abdomen was the primary donor site in most studies with fat from the thigh and flank area used in cases of insufficient supply.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All articles described, to some extent, the methods of preparing and grafting the adipose tissue (Table 2 ). 9 , 35 , 36 , 38 52 Eleven out of 14 studies used a local form of anesthesia, 9 , 36 , 38 42 , 44 46 , 48 , 49 , 51 , 52 and 3 authors preferred general anesthesia. 35 , 47 , 50 The abdomen was the primary donor site in most studies with fat from the thigh and flank area used in cases of insufficient supply.…”
Section: Resultsmentioning
confidence: 99%
“…The infiltration cannula size was poorly reported, with 3 studies 35 , 40 , 46 reporting using 1-, 2-, or 3-mm cannulas, respectively, and the infiltration solution varied widely among studies. Ten studies 9 , 35 , 40 , 41 , 45 50 (additionally) used some form of local anesthetic in combination with different solutions of epinephrine and saline before harvesting by way of manual aspiration in 16 of the 18 reporting studies. Harvesting was done by 2–3 mm cannulas, mostly blunt with 2–3 holes and attached to 10–60 ml Luer lock syringes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While studies utilizing measures, including EQ-5D, Q-LES-QA, SF-12, WHO-5, and RSES, were identified, there were either too few or numerical data not reported. The SF-36 was the only validated measure that was identified in both antidepressive and cosmetic studies that met all the exclusion and inclusion criteria, yielding five cosmetic [18][19][20][21][22] and eight antidepressant SF-36 articles 13,14,23-28 (►Fig. 1).…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%